Finite element analysis of steel-concrete composite connection with prefabricated permanent steel form - Ju, Hyunjin; Lee, Deuckhang; Choi, Dong-Uk (Journal of Asian Concrete Federation, 2022)
Composite structural members are widely used due to superior performance to traditional structural members consisting of either concrete or steel material. This study proposes steel-concrete composite beam-column connections utilizing prefabricated permanent steel form and presents a finite element analysis to ver-ify the structural performance of the system, which is based on the experimental data conducted under cyclic loading protocol simulating seismic action. Five different design specimens are covered where the key varia-bles include the asymmetric section of the steel beam, the type of the column, and the detail of longitudinal reinforcement placement. The specimens were modeled in ABAQUS with solid and truss elements for concrete and steel parts, respectively. In addition, the nonlinear material behavior of the concrete was considered in the model where the concrete damaged plasticity model was assigned. The interaction between concrete and steel was also investigated to capture the structural behavior of the specimens measured from the test. The analysis showed that the concrete section improves the structural performance of the composite beam while preventing the steel beam from bucking. The finite element analysis was not capable of catching the strength degradation at the ultimate state but provided reliable results with overall moment-story drift behavior.